(untitled) (Comprehensive Journal of Science, 2025)
The smart meter is a system that transfers data between consumer segments and the General Electricity Company. The system provides many electronic functions that were previously controlled manually, and provides energy consumption rates, enabling the electricity company to manage energy consumption. These indicators will encourage consumers to reduce energy demand during peak times by offering incentives and new prices derived from consumption times. This study aims to provide a detailed analysis of consumption periods using smart meters and propose solutions to reduce consumption and avoid load shedding. It also clarifies the consumption times of residential subscribers and calculates energy consumption in the morning and evening periods. It also highlights the importance of smart meters in reducing consumption and maximizing the economic and social returns of sustainable development (2030), through which we guarantee the rights of future generations. The study demonstrated that consumption in the evening is higher than in the morning, and that consumption costs are calculated at a rate of 25 dirhams (instalment bank system category). Monthly consumption ranges between 5 and 20 dinars, and 3 dinars are deducted monthly when the meter is recharged. We recommend issuing a new tariff for the prepaid system, as well as a tariff for peak hours, represented by the evening period, according to the findings of the study.